Factors Related to Length of Intensive Stay in Patients Post-Lower Gi Tract Operation: Literature Review - Annisa Nurmayanti S; Sommeng, Faisal; Hasir, Julia; Kurniawan, Agung; Andi Irwansyah Ahmad (Jurnal Info Sains : Informatika dan Sains, 2026)
Background: Duration of stay in the Intensive Care Unit (ICU) after lower gastrointestinal surgery is an important prognostic parameter that influences patient outcomes and the burden on hospital resources. Its determinants are multifactorial and complex, requiring identification through a systematic literature review. Objective: To identify and synthesize factors associated with the length of intensive care stay in patients after lower gastrointestinal surgery. Method: A systematic review using a narrative design was conducted. A literature search was conducted in the Google Scholar, Semantic Scholar, and PubMed NCBI databases (2015-2024). Articles were selected based on inclusion-exclusion criteria, assessed for quality, and data were extracted for thematic analysis. Results: From the 20 selected articles, the determining factors were grouped into four domains: (1) Patient Factors (comorbidity, frailty, malnutrition, psychocognitive disorders); (2) Procedure Factors (emergency surgery, anastomotic complications, long anesthesia duration, open surgical techniques); (3) Complications (nosocomial infections, delirium, renal and multiorgan dysfunction); and (4) Management & System Factors (ERAS protocols, goal-directed fluid therapy, early enteral nutrition, high-volume institutional experience). Conclusion: The length of intensive care stay after lower gastrointestinal surgery is determined by the dynamic interaction of patient factors, procedures, complications, and quality of management. Effective strategies to shorten it require a holistic approach that includes preoperative optimization, complication prevention, implementation of evidence-based protocols, and multidisciplinary collaboration.